Using ePals.com in English classes: A tool for internationalization of public elementary education in Brazil - Santiago, Maria Elizabete Villela; Dias, Reinildes (The ESPecialist, 2018)
Globalization has blurred geographical borders, allowing a multidirectional flow of cultures, languages, knowledge and actions among peoples around the world. Simultaneously, the New Information and Communication Technologies (NICTs) have enabled interactions not constrained by space and time, generating information and service offers and demands among individuals from anywhere in the world. In this scenario, both English Language (EL) and Digital Literacies have become paramount for international interactions. Despite the guidelines in UNESCO’s documents and in the Brazilian Common Core Curriculum, EL teaching in public schools is still far from meeting the needs of a global society. In this paper, I analyze the intercultural, digital, multimodal and EL literacies of a group of public school 6th graders and establish the gaps between this diagnosis and the international and national educational guidelines. Then, I present the resources offered by ePals.com as a possibility to fill the identified gaps.